Vibrational communication (drumming) of the western nearctic stonefly genus Hesperoperla (Plecoptera: Perlidae) - Sandberg, John B. (Illiesia, 2009)
The drumming signals of both species of the North American stonefly genus Hesperoperla are reported. New signals are described for H. hoguei and a new call signal character from two new populations is provided for H. pacifica. Male calls ranged in complexity from ancestral-monophasic in H. hoguei to calls containing both monophasic and derived-grouped components in H. pacifica. Intersexual communication was less specialized in H. hoguei with 2-way (male call-female answer) duets, and more specialized in H. pacifica, having both 2-way and 3-way (male-call, female-answer, male-response) exchanges.
Keywords: drumming; entomology; species dialect; Perlidae; Plecoptera; Hesperoperla; United States of America; USA; entomologija; vrbnice